Repetitive transcranial magnetic stimulation elevates the serum levels of neurotrophic factors and serotonin and its metabolites in patients with ischemic stroke - Li, Wei; Li, Wenyan; Wen, Yinghua; Wu, Junying (Frontiers in Neurology, 2025)
ObjectiveRepetitive transcranial magnetic stimulation (rTMS) can effectively treat cognitive impairment in stroke patients; however, its mechanism of action remains unclear. The aim of this study was to investigate whether rTMS improves cognitive function by regulating the levels of brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), 5-hydroxytryptamine (5-HT), and 5-hydroxyindoleacetic acid (5-HIAA).MethodsIn a 4-week study, 70 patients with ischemic stroke were randomly assigned to two groups: one received rTMS (n = 35) and the other received sham-stimulation (n = 35) in addition to conventional medication and rehabilitation training. Patients in the rTMS group were treated with rTMS at 10 Hz for 20 min per session. The Montreal Cognitive Assessment (MoCA) and response time in the n-back task were used to assess the severity of the disease. Fasting venous blood was collected in the early morning, both before and after the treatment. The peripheral blood levels of BDNF, NGF, 5-HT, and 5-HIAA were measured using the enzyme-linked immunosorbent assay (ELISA).ResultsThe levels of BDNF and NGF were higher in the rTMS group than in the sham group (p = 0.017, p = 0.008), after the rTMS treatment, and the levels of 5-HT and 5-HIAA were also elevated in the rTMS group (p = 0.049, p = 0.004). The changes in serum 5-HT and 5-HIAA levels after the rTMS treatment correlated with the changes in the MoCA and response time in the n-back task. There was a positive correlation between the serum 5-HT and BDNF levels (r = 0.4034).ConclusionOur results showed that the BDNF, NGF, 5-HT, and 5-HIAA levels were upregulated after the rTMS treatment, which likely contributed to improvements in cognitive function and quality of life in the patients with stroke.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=216761, ChiCTR2400082383.